APPLICATION OF SOME TYPES OF SEAWEEDS ON THE GROWTH AND YIELD OF SHALLOT (Allium ascalonicum L.) - Ramal Yusuf; Abdul Syakur; Budiatno Budiatno; Hidayati Mas'ud (AGROLAND: The Agricultural Sciences Journal, 2016)
Shallot plant is often used as a flavor enhancer and appetite enhancer food. Research on shallotcrop has been done. Application of seaweedsgive a different effect on increasing the productivity and growth of shallots. This study aims to determine the effect of applying different types of seaweed on growth and yield of shallot variety Lembah Palu. This research was conducted at the Green House of Faculty of Agriculture, University of Tadulako from March to May 2016. The study conducted using a randomized block design (RBD).  The treatments: B0 = control, B1 = NPK 0.2 g / pot, B2 = (Cauelerpa sp) 100 ml/pot, B3 = (Sargassum sp) 100 ml/pot, B4 = (Eucheuma cottonii) 100 ml /pot, B5 = Sea lettuce (Ulva sp) 100 ml/pot. there are six treatments, each treatment was replicated four times, so there are 24 experimental units. The results indicatedthat the application of various types of seaweed significant effect on plant height, fresh weight of the plants, the fresh weight of tuber and diameter of the bulb.